Fresh produce retail – analysis of vertical coordination and procurement models in the central California lemon supply chain - Avedian, Nathan (Kansas State University, 2018)
The fresh produce retail market is becoming increasingly competitive and the need to cut costs in order to invest in retail prices and innovations is critical. Seasonality of commodities cause market shoulders where retailers face increased prices and an insecure supply base with risk of being out of product. The implications of paying more than competitors or not having a product on the shelf can risk losing a customer’s business to a competitor. This thesis is an analysis of procurement strategies by retailers in the fresh produce industry, in order to maximize efficiency by reducing cost of goods and securing supply. Specifically, this thesis will analyze different procurement strategies for procuring lemons out of the California San Joaquin Valley. The analysis will compare traditional market buys vs a vertically integrated procurement model in which the retailer procures farm land and controls the commodity from farm to store shelf. While the fresh produce industry has had an evolution over the past century, models of procurement are not following other industries in advancements such as innovations from technology, genetics and sustainability. By advancing procurement models the industry has the potential to not only benefit farmers and retailers but also deliver the customer a fresher product at a reduced price. The objective of this project is to investigate the ways to minimize commodity costs for the retailer and gain security of supply by analyzing procurement strategies for procuring lemons from California. This project is intended to support the fresh produce supply chain and specifically the retailer to optimize their procurement model. To determine an optimal strategy this project will compare and contrast traditional market buys vs a vertically integrated strategy. This is to determine if vertically integrating this commodity in a retailer supply chain would result in a net reduction of cost. Also, this project will determine if security of supply is gained through vertical integration vs traditional market buys. This project will consider variables such as market prices, supply/demand, sustainability and other industry implications. The data examined includes retail pricing and costs, farm production and cost, property market values, and other variables and inputs. The methods of analyzing the data include profitability scenarios throughout multiple procurement models for retailers to determine an optimal procurment model. As a result of the data and methods it is determined that there is an opportunity throughout the produce supply chain for retailers to shift away from traditional procurement models. This project’s proposed land acquisition procurement model is an alternative strategy that can supplement traditional procurement model and would potentially reduce cost of goods and improve supply reliability. This vertically integrated procurement model creates supply chain efficiencies and reduces cost for the retailer along with increasing the retailer's security of supply in the fresh produce commodity market. This analysis should serve as a basis and guide for retailers to determine their company’s optimal procurement model.
Keywords: Produce; California; Land Aquisition; Procurement; Lemon; Economics